(untitled) (Journal of Atomic and Molecular Sciences, 2022)
In the present work, the excited state intramolecular proton transfer (ESIPT) process between the Enol and Keto forms of the title compound has been investigated with the time-dependent density functional theory (TDDFT) method. The geometric structures, frontier molecular orbitals, electrostatic potential (ESP) maps as well as the absorption and fluorescence spectra of the two forms of the title compound have been investigated. The calculated absorption spectra of the Keto form are more in agreement with the experimental results. Moreover, the potential energy curves of the intramolecular proton transfer (IPT) within the title compound have been scanned in both ground state S_0 and the first excited state S_1. We found that the intramolecular proton transfer from Enol form to Keto form in excited state is almost barrierless with an energy barrier 2.1 kJ/mol whereas intramolecular proton transfer between the two forms of the title compound in ground state is forbidden with energy barrier as high as 10.5 kJ/mol.